Learning in sports coaching. Theory and application (Routledge, 2016)
The facilitation of learning is a central feature of coaches` and coach educators` work. Coaching students and practitioners are, as a result, being expected to give increasing levels of thought towards how they might help to develop the knowledge and practical skills of others. Learning in Sports Coaching provides a comprehensive introduction to a diverse range of classic, critical, and contemporary theories of learning, education, and social interaction and their potential application to sports coaching. Each chapter is broadly divided into two sections. The first section introduces a key thinker and the fundamental tenets of his or her scholarly endeavours and theorising. The second considers how the theorist`s work might influence how we understand and attempt to promote learning in coaching and coach education settings. By design this book seeks to promote theoretical connoisseurship and to encourage its readers to reflect critically on their beliefs about learning and its facilitation. This is an essential text for any pedagogical course taken as part of a degree programme in sports coaching or coach education. 1. Introduction: Towards a Theoretical Connoisseurship of Learning in Sports Coaching (Lee Nelson, Ryan Groom, and Paul Potrac) Part 1: Behaviourist and Social Cognitivist Theorists 2. Burrhus Frederic Skinner: Environmental Reinforcement in Coaching (Ryan Groom, Lee Nelson, and Paul Potrac with Andy Coyles) 3. Albert Bandura: Observational Learning in Coaching (Gethin Thomas, Kevin Morgan, and Kerry Harris) Part 2: Experiential Theorists 4. John Dewey: Experience, Inquiry, Democracy, and Community in Coaching (David Day with Jackie Newton) 5. Donald Schön: Learning, Reflection, and Coaching Practice (Christine Nash) Part 3: Humanist Theorists 6. Abraham Maslow: Hierarchy of Coach and Athlete Needs (Tristan Coulter, Megan Gilchrist, and Clifford Mallett with Adam Carey) 7. Carl Rogers: Person-Centred Learning in Coaching (Chris Rowley with Callum Lester) Part 4: Constructivist Theorists 8. Jean Piaget: Learning and the Stages of Athlete Development (John Toner and Aidan Moran with Laura Gale) 9. Lev Vygotsky: Learning Through Social Interaction in Coaching (Paul Potrac, Lee Nelson, and Ryan Groom with Kenny Greenough) 10. Yrjö Engeström: Coaching, Learning, and Activity Theory (Robyn L. Jones, Gareth L. Thomas, Irineu A. Tuim Viotto Filho, Tatiane da Silva Pires Felix and Christian Edwards) 11. Ivor Goodson: Narrative Coach Learning and Pedagogy (Jennifer McMahon and Brett Smith) Part 5: Critical and Post-Structural Theorists 12. Paulo Freire: Problem-Posing Coach Education (Lee Nelson, Paul Potrac, and Ryan Groom with Claire Maskrey) 13. Jack Mezirow: Transformative Coach and Athlete Learning (William G. Taylor with Leol Collins) 14. Robin Usher: A Post-Structuralist Reading of Learning in Coaching (Luke Jones, Jim Denison, and Brian Gearity) Part 6: Social and Ethical Theorists 15.Herbert Blumer: Coaching and Learning as Symbolic Interaction (Lee Nelson, Ryan Groom, and Paul Potrac with Phil Marshall) 16.Jean Lave: Learning in Coaching as Social Praxis (Christopher Cushion with Robert Townsend) 17. Peter Jarvis: Lifelong Coach Learning (Pierre Trudel, Diane Culver, and Jean-Paul Richard) 18. Nel Noddings: Caring, Moral Learning, and Coaching (Laura Purdy, Paul Potrac, and Rutenis Paulauskas) 19. Conclusion: Recognizing the Dimensions and Tensions of Learning in Coaching (Lee Nelson, Paul Potrac, and Ryan Groom)